The Importance of Alignment Between Long-Term Planning and Short-Term Planning in Educational Institutions - Mukti; M. Sirozi (al-Afkar, Journal For Islamic Studies, 2025)
This study aims to analyze the alignment between long-range planning and short-range planning in educational institutions. This study uses a qualitative approach with a library research method, this study examines various sources of literature related to long-term and short-term planning in educational institutions. Based on the results of this study, it shows that the importance of this alignment can be seen in several aspects, such as the efficiency of resource allocation, program continuity, and the ability to adapt to change. With a clear long-term plan, educational institutions can design a short-term plan that is more directed and measurable, so as to avoid overlap or waste in the implementation of activities. In addition, periodic evaluations of the achievement of the plan are also necessary to ensure that all activities remain relevant and in accordance with the strategic objectives that have been set.through collaboration between all stakeholders, including teachers, students, and parents, educational institutions can create a more responsive and innovative learning environment. This alignment not only improves the quality of education but also builds a strong foundation for the future development of the institution.